Participation of parents in the humanization of children's stay in hospitals - Ranković Dragica; Jovčić Ljiljana; Trbović Verica; Jezdimirović Danijela (Association of Nurses Technicians and Midwives, 2022)
Successful treatment of a child depends not only on the severity of the disease, but also on the child's attitude towards the disease and its treatment. In this regard, in addition to the treatment and health care of the child, it is necessary to provide psycho-social support, which is also needed by their parents, through the availability of information and counseling. Having in mind the specificity of the hospital context, it is considered that children suffering from chronic diseases have a higher level of awareness and understanding in relation to the population of the same age in the outpatient environment. Parents and health workers are the first to notice the concept of humanization of children in hospitals and give more importance to the characteristics of children with chronic diseases compared to those who have an acute emergency. Although the legal framework regulates children's health care in terms of decision-making, parents are traditionally considered key actors in decision-making on behalf of the child, primarily because they know what is best in his interest. Special attention in this paper is focused on the positive effects of involving parents, as members of the health team, in the psychological preparation of children for hospitalization or for some other medical procedures that await them in the hospital context.